Is Islamic Economy as that Green? - Budhi Fatanza Wiratama; Zasya Safitri (AL-MUZARA'AH, 2023)
Economic growth is widely associated with degradation of environmental quality. Green economy is a term that later emerged to save the environment. In Islamic point of view, the environment and the economy are two things that must support each other. This study discusses Islamic economics that should be associated with sustainability, as in line with the teachings of Islam to coexist with the environment. The method used are correlation analysis and panel data regression to find out the association between Islamic economics and green growth in major Islamic economic countries. The results show that the Global Islamic Economy Indicator (GIEI) is positively correlated to the Green Growth Index (GGI). Based on the panel data regression model, Muslim Modest Fashion sector significantly has a positive effect on GGI. Unfortunately, in general, the GGI achievements of the OIC countries are still very lacking compared to non-OIC countries. It is the government's duty to start implementing environmentally oriented policies in all sectors of the Islamic economy inclusively.